2022
DOI: 10.26668/businessreview/2022.v7i3.e655
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and GCG Disclosure on Firm Value with Profitability

Abstract: Purpose: The CSR program is one of the efforts made by the company to have a positive impact on the community as a result of the company's operational activities. Furthermore, the CSR programs that have been implemented provide information to shareholders that can be used to assess the firm's future survival. This study aims to scrutinize the CSR and GCG’s effects on firm value as well as verify if profitability either strengthens or weakens CSR and GCG on firm value.   Research design, data and methodology: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…This study's results align with research conducted by Sabatini & Sudana (2019), which explains that corporate social responsibility has a significant negative effect on firm value. On the other hand, this study is not in line with research conducted by Riyadh et al (2022), which found that corporate social responsibility has a significant positive effect on firm value.…”
Section: Effect Of Corporate Social Responsibility On Firm Valuecontrasting
confidence: 99%
“…This study's results align with research conducted by Sabatini & Sudana (2019), which explains that corporate social responsibility has a significant negative effect on firm value. On the other hand, this study is not in line with research conducted by Riyadh et al (2022), which found that corporate social responsibility has a significant positive effect on firm value.…”
Section: Effect Of Corporate Social Responsibility On Firm Valuecontrasting
confidence: 99%
“…This aligns with the Good Management Theory statement that CSR is related to the company's financial performance (Budi, 2021). (Riyadh, Al-Shmam, and Firdaus 2022) and (Hermawan et al 2023) state that CSR has a significant effect on financial performance in Indonesian companies. Islamic banks are required to publish ICSR reports on the website of each bank so that the public can find out information, which hopefully can increase public trust.…”
Section: Introductionsupporting
confidence: 81%
“…The p-value of GCG at financial performance is (0.000 < 0.05); beta 0.334 and t value 5.204 then it can be drawn GCG has positive significant effects at financial performances, H2 proved. GCG where each individual is motivated by his own interests so that it can cause conflict between principals and agents (Riyadh et al, 2022). This encourages the existence of GCG to be placed in an honorable position.…”
Section: Resultsmentioning
confidence: 99%